2020
DOI: 10.3390/ma13071736
|View full text |Cite
|
Sign up to set email alerts
|

Application of Atomic Force Microscope to Investigate the Surface Micro-Adhesion Properties of Asphalt

Abstract: The surface energy and bonding coefficient of asphalt are important factors that affect the adhesion performance of asphalt/aggregate. In this study, the micro-bee-like-structure of asphalt and force curves between the microscope-probe and asphalt were measured via atomic force microscopy (AFM). To investigate the influence of asphalt properties on micro-adhesion of asphalt, five types of asphalt were used in four states: original, aged at 163 °C, immersed in water and added anti-stripping agent. The results d… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

0
3
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 16 publications
(3 citation statements)
references
References 27 publications
0
3
0
Order By: Relevance
“…Lv et al [12,13] experimentally found that SBS, polyethylene, and rubber powder negatively afect modifed asphalt's adhesion properties. Some scholars have used AFM observations to fnd that graphene oxide can change asphalt microstructure and enhance asphalt-aggregate adhesion [14,15]. Incorporating an antistripping agent can signifcantly improve the adhesion between asphalt and aggregate while afecting the project cost [16,17].…”
Section: Introductionmentioning
confidence: 99%
“…Lv et al [12,13] experimentally found that SBS, polyethylene, and rubber powder negatively afect modifed asphalt's adhesion properties. Some scholars have used AFM observations to fnd that graphene oxide can change asphalt microstructure and enhance asphalt-aggregate adhesion [14,15]. Incorporating an antistripping agent can signifcantly improve the adhesion between asphalt and aggregate while afecting the project cost [16,17].…”
Section: Introductionmentioning
confidence: 99%
“…The sessile drop method [13,14] and Wilhelmy-plate method [15] are commonly for testing. Recently, Atomic Force Microscopy (AFM) has been used to analyze the microstructure and mechanical properties of asphalt for surface energy testing [16][17][18]. Testing the surface energy does not allow the direct use of aggregates with real textures for testing, as serious contact angle hysteresis will occur and influence the test results [19].…”
Section: Introductionmentioning
confidence: 99%
“…Many advanced tests and simulations can be performed to evaluate the quality of the binder-aggregate bonding, such as X-ray photoelectron spectroscopy (XPS) [19,25]; energy dispersive X-ray (EDX) [25]; active adhesion evaluation method (AAEM) [10]; atomic force microscopy (AFM) [26,27]; binder bond strength (BBS) [28]; scanning electron microscopy (SEM) with energy disperse spectroscopy (EDS) [17]; infrared spectroscopy (IR) [13]; optical microscopy (OM) [29], hyperspectral imaging/digital image processing (DIP) [30] and molecular dynamics simulation (MDS) [16,21,24]; in addition to other test methods described by Mehrara et al [2].…”
Section: Introductionmentioning
confidence: 99%